New doxorubicin-loaded phospholipid microbubbles for targeted tumor therapy: Part I - Formulation development and in-vitro characterization - Tinkov, Steliyan; Winter, Gerhard; Coester, Conrad; Bekeredjian, Raffi (Journal of controlled release, 2010)
Despite high antitumor efficacy and a broad application spectrum, clinical treatment with anthracycline chemotherapeutics is often limited by severe adverse effects such as cardiotoxicity and myelosupression. In recent years, tumor drug targeting has evolved as a promising strategy to increase local drug concentration and reduce systemic side effects. One recent approach for targeting solid tumors is the application of microbubbles, loaded with chemotherapeutic drugs. These advanced drug carriers can be safely administered to the patient by intravenous infusion, and will circulate through the entire vasculature. Their drug load can be locally released by ultrasound targeted microbubble destruction. In addition, tumors can be precisely localized by diagnostic ultrasound since microbubbles act as contrast agents. In the present work a novel microbubble carrier for doxorubicin has been developed and characterized in-vitro. In contrast to many recent tumor-targeting MB designs the newly developed doxorubicin-loaded microbubbles possess a soft but stable phospholipid monolayer shell. Importantly, the active drug is embedded in the microbubble shell and is complexed to the phospholipids by both electrostatic and hydrophobic interactions. Despite their drug load, these novel microbubbles retained all important physical characteristics for ultrasound targeted microbubble destruction, comparable with the commercially available ultrasound contrast agents. In cell culture studies doxorubicin-loaded microbubbles in combination with ultrasound demonstrated an about 3 fold increase of the anti-proliferative activity compared to free doxorubicin and doxorubicin-loaded liposomes. For the first time in the literature the intracellular partition of free doxorubicin and phospholipid-complexed doxorubicin were compared. In conclusion, new doxorubicin-loaded microbubbles with ideal physical characteristics were developed. In-vitro studies show enhanced cytotoxic activity compared to free doxorubicin and doxorubicin-loaded liposomes.
Gesehen am 24.11.2023